Dynamic Bending Behaviour of Sandwich Structures for Marine Applications - Norman Osa-uwagboe; Vadim V. Silberschmidt; Emrah Demirci (Applied Sciences)
This paper examines the mechanical performance of fibre-reinforced composite sandwich structures (FRPSSs) for maritime applications, focusing on the impact bending and damage sequence after seawater exposure. Glass-fibre/epoxy facesheets with various PVC foam core configurations underwent low-velocity single and multiple impacts. An in situ moisture-uptake methodology monitored moisture ingress until saturation. Results showed moisture uptake reduced impact bending capacity and bending stiffness to varying degrees. While energy-absorption performance remained largely unchanged under single impacts, significant differences were noted for multiple impacts. Failure analysis confirmed the reductions in some damage modes such as facesheet fracture, indentation, and core shear failures, while core shearing, delamination, core/facesheet debonding, and fibre breakage were identified as the main failure modes. These insights enhance understanding and optimisation of FRPSSs for improved out-of-plane damage resistance in marine applications.